CORPORATE TAX POLICY AND INDUSTRY LOCATION WITH FULLY ENDOGENOUS PRODUCTIVITY GROWTH. (15th November 2017) - Davis, Colin; Hashimoto, Ken‐ichi
Abstract : This paper considers how national corporate tax policy affects productivity growth through adjustments in geographic patterns of industry in a two‐country model of trade. With trade costs and imperfect knowledge spillovers between countries, production concentrates partially and innovation concentrates fully in the country with the lowest tax rate. A rise in the international corporate tax differential accelerates productivity growth through an increase in the production share of the low‐tax country that improves knowledge spillovers from industry to innovation. The paper also investigates the relationship between the corporate tax differential and the level of market entry, and analytically characterizes the effects of changes in tax policy on national welfare. ( JEL F43, O30, O40, R12)